Feasibility Study of Particulate Extracellular Matrix (P-ECM) and Left Ventricular Assist Device (HVAD) Therapy in Chronic Ischemic Heart Failure Bovine Model. Issue 2 (March 2015) - Soucy, Kevin G.; Smith, Erin F.; Monreal, Gretel; Rokosh, Gregg; Keller, Brad B.; Yuan, Fangping; Matheny, Robert G.; Fallon, Anna M.; Lewis, Beecher C.; Sherwood, Leslie C.; Sobieski, Michael A.; Giridharan, Guruprasad A.; et al.
<x xml:space="preserve">Abstract</x> Myocardial recovery with left ventricular assist device (LVAD) support is uncommon and unpredictable. We tested the hypothesis that injectable particulate extracellular matrix (P-ECM) with LVAD support promotes cell proliferation and improves cardiac function. LVAD, P-ECM, and P-ECM + LVAD therapies were investigated in chronic ischemic heart failure (IHF) calves induced using coronary embolization. Particulate extracellular matrix emulsion (CorMatrix, Roswell, GA) was injected intramyocardially using a 7 needle pneumatic delivery tool. Left ventricular assist devices (HVAD, HeartWare) were implanted in a left ventricle (LV) apex to proximal descending aorta configuration. Cell proliferation was identified using BrdU (5 mg/kg) injections over the last 45 treatment days. Echocardiography was performed weekly. End-organ regional blood flow (RBF) was quantified at study endpoints using fluorescently labeled microspheres. Before treatment, IHF calves had an ejection fraction (EF) of 33 ± 2% and left ventricular end-diastolic volume of 214 ± 18 ml with cardiac cachexia (0.69 ± 0.06 kg/day). Healthy weight gain was restored in all groups (0.89 ± 0.03 kg/day). EF increased with P-ECM + HVAD from 36 ± 5% to 75 ± 2%, HVAD 38 ± 4% to 58 ± 5%, and P-ECM 27 ± 1% to 66 ± 6%. P-ECM + HVAD demonstrated the largest increase in cell proliferation and end-organ RBF. This study demonstrates the feasibility of combined LVAD support with P-ECM injection to stimulate new cell proliferation and improve cardiac function, which warrants further investigation.